Knowledge and Implementation of Integrated Management of Childhood Illness at East Kalimantan - Zulaikha, Fatma; Triasih, Rina; Purwanta, Purwanta (Department of Public Health, Faculty of Sport Science, Universitas Negeri Semarang, 2018)
Pneumonia is the most common cause of morbidity and mortality among young children worldwide. Integrated Management of Childhood Illness (IMCI) is a procedural form in the care of childhood illness which aims to minimize morbidity and mortality rate in children, including pneumonia. This was a cross-sectional study at Samarinda and Kutai Kartanegara community health center from July to October 2015. The health workers’ knowledge was assessed through questionnaire. The quality of IMCI implementation was evaluated through direct observation in primary health care. A total of 46 health workers were involved in this study. Observation of IMCI implementation quality was conducted in 104 children. The majority of respondents (73.9) had sufficient knowledge; however, in terms of direct implementation on the field, most of the respondents (87%) were included in incompetent category. It can be concluded that level of knowledge was related to implementation of cough IMCI in community health center, but the correlation was weak.